Effect of increased wind penetration on system prices in Korea's electricity markets. (21st June 2013) - Shcherbakova, Anastasia; Kleit, Andrew; Blumsack, Seth; Cho, Joohyun; Lee, Woonam
ABSTRACT In this paper, we examine the effect of increased wind penetration on system marginal prices (SMPs) in South Korea's electricity market. Korea's renewable portfolio standard (RPS) went into effect in 2012, with a goal of increasing the share of renewable generation to 10% of the total load by 2022. We examine the output of wind installations across the Korean peninsula and simulate an increase in wind penetration consistent with Korea's RPS targets. Under a variety of assumptions on demand elasticity, we find that higher shares of wind generation in total supply reduce both the average SMP and its variation. In particular, we find that wind energy output on the Korean peninsula is more correlated with peak electricity demand than has been reported for other regions. The per‐unit value of wind energy to owners of wind assets is thus higher for South Korea than would be the case for European or North American locations with a similar mix of fuels other than wind. Copyright © 2013 John Wiley & Sons, Ltd.